2017
DOI: 10.1097/nna.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Interruptions in a Trauma Intensive Care Unit

Abstract: A deeper understanding of individual factors and their complex interactions related to interruptions experienced by ICU RNs are vital to understanding the clinical significance of these interruptions and intervention design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 17 publications
0
21
0
10
Order By: Relevance
“…Over time, this may develop a fundamental common condition among staff not to miss out on anything. The consequence may be that nurses interrupt colleagues anywhere, at anytime with anything, either to be more time effective, as part of mentoring, to speed up a work process or because of other urgent or important matters (Berg, Florin, et al., ; Craker et al., ; Monteiro et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, this may develop a fundamental common condition among staff not to miss out on anything. The consequence may be that nurses interrupt colleagues anywhere, at anytime with anything, either to be more time effective, as part of mentoring, to speed up a work process or because of other urgent or important matters (Berg, Florin, et al., ; Craker et al., ; Monteiro et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The above mentioned can lead to stress and force nurses to develop strategies to maintain and keep up with the work pace (Monteiro et al., ) and may result in forgetfulness, reduced job satisfaction and other stress‐related symptoms (Filer et al., ; Tucker & Spear, ; Werner & Holden, ). However, interruptions may be positive when contributing to share essential knowledge to increase the quality of care (Craker et al., ; McCurdie, Sanderson, Aitken, et al. ; Prates Dde & Silva, ).…”
Section: Introductionmentioning
confidence: 99%
“…27 It should be emphasized that the four studies that discussed the exchange of information as important pointed out the alert to professionals regarding the continuity of an unsafe act, that is, the interception of errors, that prevents the harm to the patient. 13,16,19,21 A Brazilian study was identified that reports that interruptions, besides preventing errors, help the professional to be more precise in their activities. 4 Another positive point of the interruption, understood as a factor that makes the efficiency of the work process feasible, while other studies approach interruption as an action that increases the problem-solving capacity.…”
Section: Level IVmentioning
confidence: 99%
“…14,16,24 The reduction of clinical performance, efficiency, effectiveness and productivity of the professional is emphasized. 10,13,15,19, The increase in nurses' workload is indicated as a consequence of the interruption. 10-2; 24 It complements, in a Swiss study, that, when finishing the secondary activity, the professional demands certain time to resume the initial task, which causes an increase of the work load.…”
Section: Level IVmentioning
confidence: 99%
See 1 more Smart Citation